General Characteristics and Risk Factors of Cardiovascular Disease among Interstate Bus Drivers - Raquel Pastréllo Hirata; Luciana Maria Malosa Sampaio; Fernando Sergio Studart Leitão Filho; Alberto Braghiroli; Bruno Balbi; Salvatore Romano; Giuseppe Insalaco; Luis Vicente Franco de Oliveira (The Scientific World Journal)
Workers in the transportation industry are at greater risk of an incorrect diet and sedentary behavior. The aim of our study was to characterize a population of professional bus drivers with regard to clinical and demographic variables, lipid profile, and the presence of cardiovascular risk factors. Data from 659 interstate bus drivers collected retrospectively, including anthropometric characteristics, systolic and diastolic blood pressure, lipid profile, fasting blood glucose, meatoscopy, and audiometry. All participants were male, with a mean age of 41.7±6.9 years, weight of 81.4±3.3 kg, and BMI 27.2±3.3 Kg/m2; the mean abdominal and neck circumferences were 94.4±8.6 cm and 38.9±2.2  cm; 38.2% of the sample was considered hypertensive; mean HDL cholesterol was 47.9±9.5 mg/dL, mean triglyceride level was 146.3±87.9 mg/dL, and fasting glucose was above 100 mg/dL in 249 subjects (39.1%). Drivers exhibited reduced audiometric hearing at 4–8 kHz, being all sensorineural hearing loss. The clinical characterization of a young male population of interstate bus drivers revealed a high frequency of cardiovascular risk factors, as obesity, hypertension, hyperlipidemia, and hyperglycemia, as well as contributing functional characteristics, such as a low-intensity activity, sedentary behavior, long duration in a sitting position, and high-calorie diet, which lead to excessive weight gain and associated comorbidities.